0864 A Randomized Controlled Trial of Light Therapy for Insomnia Symptoms in Fatigued Cancer Survivors. (27th April 2018) - Garland, S N; Johnson, J A; Carlson, L E; Rodriguez, N; Savard, J; Campbell, T
Abstract: Introduction: Cancer-related fatigue (CRF) and insomnia are highly comorbid, suggesting that these two symptoms may share physiological, psychological, and behavioral mechanisms. The objective of this secondary analysis was to examine the impact of a 4-week light therapy intervention on insomnia severity in cancer survivors with clinical levels of fatigue. Additional outcomes included self-reported sleep quality and sleep continuity, assessed with sleep diary and actigraphy. Methods: This 4-week randomized controlled trial recruited post-treatment cancer survivors who met ICD-10 criteria for CRF. Participants were randomly assigned to a light therapy device that produced either bright white light (BWL; treatment) or dim red light (DRL; active control). The devices were used daily for 30 minutes upon waking for 28 days. Participants completed the Insomnia Severity Index at baseline, week 2, and week 4, and completed the Pittsburgh Sleep Quality Index, sleep diaries (one week), and actigraphy (one week) both at baseline and during week 4. Adherence was tracked using integrated device loggers. Results: A total of 81 participants were randomly assigned to receive BWL (n=42) or DRL (n=39). Linear mixed models analyses revealed a significant group-by-time interaction for insomnia symptoms, F(2, 152.2)=3.51, p=.032. Insomnia severity improved from baseline to week 2 and from baseline to post-intervention in both groups; however, BWL condition continued to improve after 2 weeks, whereas symptoms in the DRL group began to worsen after week 2, though this was not significant. Both groups reported improvements in sleep quality (p<.001), reduction in diary measured sleep onset latency (p<.01), and improved sleep efficiency (p<.001), and actigraphy measured nocturnal wake time (p<.05). Conclusion: A 4-week light therapy intervention improved sleep parameters in clinically fatigued cancer survivors, but there was no difference between the two intervention conditions. Future research is warranted to explore this effect in cancer survivors with CRF and diagnosed insomnia disorder. Support (If Any): Canadian Cancer Society Research Institute, Innovation Grant #: 2012–701425.